2006
DOI: 10.1038/sj.jes.7500518
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, cereal consumption, and supplementation affect cadmium content in breast milk

Abstract: Breast milk might be a source of potentially toxic metals such as cadmium (Cd). The purpose of the present study is to provide data pertaining to the influence of maternal lifestyles on Cd concentrations in breast milk in the Austrian setting. Breast milk was obtained from 124 Austrian women. Each participant provided 10 ml of milk. A second group of eight mothers were recruited to investigate changes in their milk cadmium levels at 1, 3, 5, 7 and 9 weeks post partum. The study participants filled a questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 41 publications
(35 reference statements)
1
11
0
1
Order By: Relevance
“…Gundacker et al (2007) showed that breast milk samples of Austrian subjects contained, on average, a cadmium content of 0.086 μg/L and that breast milk cadmium content was lower among nonsmokers who took vitamins and mineral supplements ( p < 0.05). In a study by Kippler et al (2008), the median cadmium level in breast milk from Bangladeshi subjects was 1.6-fold higher than was the level from Austrian subjects.…”
Section: Cadmium Exposure and Effects Observedmentioning
confidence: 99%
“…Gundacker et al (2007) showed that breast milk samples of Austrian subjects contained, on average, a cadmium content of 0.086 μg/L and that breast milk cadmium content was lower among nonsmokers who took vitamins and mineral supplements ( p < 0.05). In a study by Kippler et al (2008), the median cadmium level in breast milk from Bangladeshi subjects was 1.6-fold higher than was the level from Austrian subjects.…”
Section: Cadmium Exposure and Effects Observedmentioning
confidence: 99%
“…Gundacker et al 46 showed that breast milk samples of Austrian subjects contained, on average, a cadmium content of 0.086 μg/L and that breast milk cadmium content was lower among nonsmokers who took vitamins and mineral supplements (p < 0.05). In a study by Kippler et al 49 , the median cadmium level in breast milk from Bangladeshi subjects was 1.6-fold higher than was the level from Austrian subjects.…”
Section: Cadmium Exposure and Effects Observedmentioning
confidence: 99%
“…However, recent studies have raised the concern that human breast milk might be contaminated with heavy metals such as cadmium (Cd) and lead (Pb). Lead and/or cadmium have been recently measured in breast milk or colostrum of lactating mothers in many countries including Saudia Arabia [1], Brazil [2], Austria [3], Bangladesh [4] and Japan [5, 6].…”
Section: Introductionmentioning
confidence: 99%